Evaluation of Toxins, Antinutrients and Nutrients of Indian Cultivating Varieties of Jatropha curcas - Pasha, Chand; Balakrishna, Kannoju; Hanumalal, Nunavath; Srinivas, Banoth; Chandrasekhar, Banoth (Asian Journal of Chemistry, 2012)
Jatropha curcas a member of the euphorbiaceae family is a multipurpose shrub of significant economic importance because of its several biofuel and medicinal uses. The seeds contain high oil, which can be used as fuel directly or as a substitute to diesel in the transesterified form. The seed cake can be a good protein source for humans as well as for livestock, but highly toxic to a number of animal species due to the presence of toxins and antinutrient components. There is a variation in toxic, antinutrient and nutrient components in toxic, non toxic, wild and cultivable varieties. Seed, seed cake, leaves, fruits, oil and latex samples of 15 cultivating J. curcas varieties were collected across the India for toxins, antinutrient and nutrient characterization. The average content of principal toxin phorbol esters is 7.70 mg/g in seed, 4.24 mg/g in seed cake, 2.9 mg/g in oil and 0.73 mg/g in latex. phorbol esters were not found in young leaves and concentration was found to be increasing in leaves and fruits as age increases till a month. Curcin, phytate, trypsin inhibitor, saponin and total phenols are less than the non toxic Mexican varieties. Total protein in seed is 21 to 30 %, whereas in screw pressed seed cake it is 25 to 34 %. With increase in protein content decrease in oil content was observed.